2023
DOI: 10.1002/cem.3472
|View full text |Cite
|
Sign up to set email alerts
|

Noise simulation in classification with the noisemodel R package: Applications analyzing the impact of errors with chemical data

Abstract: Classification datasets created from chemical processes can be affected by errors, which impair the accuracy of the models built. This fact highlights the importance of analyzing the robustness of classifiers against different types and levels of noise to know their behavior against potential errors. In this context, noise models have been proposed to study noise‐related phenomenology in a controlled environment, allowing errors to be introduced into the data in a supervised manner. This paper introduces the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Another recent comprehensive review of diferent methods of adding noise to class variable, attribute variables, or both in combination is given by Sáez [28]. Sáez has also presented an R package which is called noisemodel [29]. Tis R package contains diferent ways for adding noise to class variable, attribute variables, and both in combination.…”
Section: Adding Noise Methodsmentioning
confidence: 99%
“…Another recent comprehensive review of diferent methods of adding noise to class variable, attribute variables, or both in combination is given by Sáez [28]. Sáez has also presented an R package which is called noisemodel [29]. Tis R package contains diferent ways for adding noise to class variable, attribute variables, and both in combination.…”
Section: Adding Noise Methodsmentioning
confidence: 99%
“…Conducting further studies could also provide a more nuanced understanding of PU development over time, considering factors such as lesion severity and changes in patient characteristics. Moreover, as inaccuracies can impact the performance, complexity, and construction time of classifiers [53], investigating different data preprocessing techniques becomes relevant. Addressing issues such as class overlapping or noise through approaches like noise filters [54] could contribute to further improvements in the models created.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Garcia et al [10] demonstrated the its efficacy in replicating noise patterns observed in real-world datasets, confirming its statistical properties and impact on model performance. Multiple empirical studies have shown that the Neighborwise method enhances the robustness of ML models by providing a realistic basis for evaluating noise filters [38]. In the current work, we utilized the Neighborwise method to create controlled yet realistic noise conditions to improve the accuracy and robustness of our noise filter and hyperparameter recommendations for CNL tasks.…”
Section: Noise Imputationmentioning
confidence: 99%